Nurses' views of fundamental relational skills used in clinical practice: a cross-sectional pilot study - Timmins Fiona; de Vries Jan M. A.; Muldowney Yvonne; Mc Cabe Catherine; Whelan Jacqueline; Buckley Sinéad; McCarthy Sandra (Sciendo, 2021)
Effective communication skills are one of the core competencies of nursing curricula internationally. Nurses are generally regarded as proficient. Despite our complete trust in the profession, deficiencies and gaps exist. However, it is not clear to which extent nurses use key communication skills in practice, and whether or not confident in using these skills compounds environmental issues that occur. This study explored nurse's confidence and application of relational skills competencies in nursing practice.